Simultaneous and Direct Determination of As, Bi, Pb, Sb, and Se and Co, Cr, Cu, Fe, and Mn in Milk by Electrothermal Atomic Absorption Spectrometry - Freschi, Gian Paulo G.; Fortunato, Felipe M. [UNESP]; Freschi, Carolina D. [UNESP]; Gomes Neto, José Anchieta [UNESP] (Springer, 2012)
Tungsten permanent modifier with coinjection of Pd(NO3)(2) and W-Ru permanent modifiers are proposed for the direct and simultaneous determination of As, Bi, Pb, Sb, and Se (group 1) and Co, Cr, Cu, Fe, and Mn (group 2), respectively, in milk by graphite furnace atomic absorption spectrometry. The performance of modifiers was evaluated by means of thermal behavior of analytes, sensitivity, atomic signal profile, repeatability, graphite tube lifetime, and background intensity. An air-assisted pyrolysis step was necessary to quantitative elimination of the organic matter. After methods optimization, 14 commercial milk samples were analyzed. The found concentrations of As, Bi, Pb, Sb, Se, Co, and Cr were lower than their limit of detection (2.13, 2.21, 1.49, 1.63, 2.05, 1.0, and 1.2 mu g L-1, respectively). Concentrations of Cu, Fe, and Mn were in the 1.58-5.74 mu g L-1, 9.79-49.3 mu g L-1, and 2.25-4.08 mu g L-1 intervals, respectively. The limits of detection for Cu, Fe, and Mn were 1.7, 5.3, and 2.0 mu g L-1, respectively. The accuracy of methods was checked after analysis of two milk standard materials. Results for Cr, Cu, Fe, Mn, Pb, and Mn were in agreement with certified values of SRMs at the 95% confidence level. Accuracy was also evaluated by addition-recovery tests and recoveries in the 86-127% range were obtained for all elements. The use of pretreat platform of graphite tubes with W or W-Ru allowed enlarging the lifetime of atomizer in 750 heating cycles.
Keywords: Milk analysis; Direct and simultaneous determination; Permanent modifiers; GFAAS